Pengembangan Literasi Anak Pegunungan dengan Cerita Bergambar Melalui Komik Peduli Lingkungan - Hasnur Ruslan; Syahrul Saehana; Syamsyuddin Syamsyuddin; Ulfah Ulfah; Arum Pujining Tyas (Pusat Riset dan Inovasi Nasional, 2025)
Children growing up in mountainous areas generally live in close contact with nature. They encounter forests, rivers, gardens, and rice fields daily. However, such proximity does not always lead to an understanding of the importance of protecting and preserving the environment. In Vatambaya Hamlet, Kalora Village, Donggala Regency, for instance, many children are still not accustomed to reading, have limited access to reading materials relevant to their daily lives, and are unfamiliar with simple stories that can convey the value of caring for nature. Yet, childhood is the most appropriate period to instill good habits, including a love for the environment. Therefore, it is considered necessary to provide a simple yet engaging learning medium: environmental comics. Comics were chosen because they are appealing to children colorful, filled with relatable characters, and built around stories that are easy to follow. Through pictures and narratives, messages about protecting rivers, planting trees, sorting waste, and caring for the soil can be delivered in a light yet impactful manner. The aim of this study is to enhance children’s basic literacy skills, particularly in reading and comprehending simple texts.